Formulation and Evaluation of Lip balm Containing Ethanolic Extracts of Moringa oleifera and Muntingia calabura Leaves - Winioliski L. O. Rohi Bire; Delila Seli Keba; Serlibrina Wulandari Turwewi; Maria Nuari Putri Wadhi (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Lip balm is a topical preparation used to maintain moisture and protect the lips from various environmental factors. The use of natural ingredients in lip balm has increased and is considered safer. Cherry leaves (Muntingia calabura) and moringa leaves (Moringa oleifera) are known to contain various secondary metabolites with potential applications in cosmetic formulations. This study aimed to formulate a lip balm based on a combination of ethanolic extracts of cherry and moringa leaves and to evaluate its physical stability. The formulation was evaluated through physical stability tests, including organoleptic properties, homogeneity, pH, and spread ability. Stability testing was conducted at room temperature for 14 days, with observations performed on days 0, 7, and 14. The results showed that all formulations exhibited good organoleptic characteristics, were homogeneous, and did not undergo significant changes during storage. It can be concluded that the lip balm formulation containing a combination of ethanolic extracts of cherry (Muntingia calabura) and moringa (Moringa oleifera) leaves demonstrated good physical stability and has potential for further development as a natural-based cosmetic product.